Do animals bite more during a full moon? Retrospective observational analysis. Issue 7276 (23rd December 2000) - Bhattacharjee, Chanchal; Bradley, Peter; Smith, Matt; Scally, Andrew J; Wilson, Bradley J
Abstract: Objective: To test the hypothesis that the incidence of animal bites increases at the time of a full moon. Design: Retrospective observational analysis. Setting: Accident and emergency department at a general hospital in an English city. Subjects: 1621 consecutive patients, irrespective of age and sex. Main outcome measures: Number of patients who attended an accident and emergency department during 1997 to 1999 after being bitten by an animal. The number of bites in each day was compared with the lunar phase in each month. Results: The incidence of animal bites rose significantly at the time of a full moon. With the period of the full moon as the reference period, the incidence rate ratio of the bites for all other periods of the lunar cycle was significantly lower (P <0.001). Conclusions: The full moon is associated with a significant increase in animal bites to humans.